Policy Development and Advocacy: The Analysis of a Paid Family Leave Bill in the Hawaii State Legislature - Jing Guo; Hua Zan (Social Work & Society, 2018)
As an important support for work-family balance, paid family leave has gained public interest and momentum at both the state and federal levels. This study focuses on paid family leave in Hawaii, a state where families face the challenges of a high cost of living and parents struggle to balance their employment and child care. We conducted a content analysis using legislative bills and written testimonies as data sources to analyze SB2961, A Bill for an Act Related to Paid Family Leave, proposed at the 2016 Hawaii State Legislature. We discuss the legislative process and identify key stakeholders and critical issues in advancing paid family leave in Hawaii. We conclude with suggestions for  continuing efforts in the policy development and advocacy of paid family leave in the state and beyond.